Legal regulation of the Ukrainian language as the state language in the Ukrainian education sphere (Law and Safety, 2023)
The constitutional status of the Ukrainian state language as a consolidating component of Ukrainian society from 1991 to the present day has been analyzed in the article. The significance of the search for spiritual associations uniting the modern community is represented. The law cannot be separated from explorations of spiritual kinship and from the rise of a certain ideology that ensures the development of the nation state. It has been noted that the leading place in the system of connecting links belongs to the Ukrainian language. A distinction between “state language” and “official language” has been made. The issue of legal regulation of the use of the state language of Ukraine in the educational sphere from the moment Ukraine was declared an independent democratic state to the present day has been studied. The language status of education at the appropriate level based on the Law of Ukraine “On Education”, State Standards of all levels of education, the Law of Ukraine “On Ensuring the Functioning of the Ukrainian Language as a State Language” has been analyzed. It has been emphasized that in accordance with the above-mentioned laws and regulatory documents, all levels of education indicated in the standards approved after the entry into force of the Law of Ukraine “On Education” can be obtained exclusively in the state language of Ukraine. It has been noted that among the key competences of preschool education and primary education, the ability to communicate in foreign languages and the native language, if the latter differs from the state, is singled out. It has been stressed that it is mandatory to study the state language of Ukraine in educational institutions of all levels.
Keywords: the Ukrainian language; state language; native language; education; law; language legislation.